Egg tanning improves the efficiency of CRISPR/Cas9-mediated mutant locust production by enhancing defense ability after microinjection - Ting-ting ZHANG; Ting-mei WEN; Yang YUE; Qiang YAN; Er-xia DU; San-hong FAN; Siegfried ROTH; Sheng LI; Jian-zhen ZHANG; Xue-yao ZHANG; Min ZHANG (Journal of Integrative Agriculture, 2021)
The mutant efficiency and hatching ratio are two key factors that significantly affect the construction of genome-modified mutant insects. In the construction of CRISPR/Cas9-mediated dsLmRNase2–/– mutant locusts, we found that the tanned eggs which experienced a 20-min contact with the oocyst exhibited a higher success rate compared to fresh newly-laid eggs that were less tanned. However, the heritable efficiency of the dsLmRNase2 deletion to the next generation G1 progeny was similar between adults derived from the tanned or less tanned engineered eggs. Further, the similar effective mutant ratios in the normally developed eggs and G0 adults of tanned and less tanned eggs also indicated that tanning did not reduce the absolute mutation efficiency induced by CRISPR/Cas9. Moreover, we found that the syncytial division period, which was longer than the time for tanning, conferred a window period for microinjection treatment with efficient mutation in both tanned and less tanned eggs. We further found that tanned eggs exhibited a higher hatching rate due to a reduced infection rate following microinjection. Both the anti-pressure and ultrastructure analyses indicated that the tanned eggs contained compressed eggshells to withstand increased external pressure. In summary, tanned eggs possess stronger defense responses and higher efficiency of genome editing, providing an improved model for developing Cas9-mediated gene editing procedures in locusts.